Analytical Studies of the Iron and Manganese Complexes of 7-Nitroso -8- Hydroxyquinoline -5-Sulphonic Acid (Journal of Science and Technology, 2016)
The ligand 7-nitroso-8-hydroxyquinoline-5-sulphonic acid (H2L) possesses the coordination sites of 2 -nitroso-1- naphthol and of 8-hydroxyquinoline, where the hydroxyl group is functional at either site. The absorption maximum of the complex formed with iron and Mn is at 700nm, at which wavelength the mole extinction coefficient of Fe(H2L)3 is 27,540 dm3 mol-1 and Mn(H2L)3 is 44,500 dm3 mol-1 respectively. The stoichiometry of H2L reagent with the metal ions by the method of continuous variation gave the ratio of iron to ligand as 1:3 and manganese to Ligand as 1:3. Chemical analysis, and physicochemical evidence are compatible with formulating the Fe(II) and Mn (II) complexes as H[M(HL)3] where the 2-nitroso–1-naphthol site is involved in metal chelation.